Work, malaise, and well-being in Spanish and Latin-American doctors - Ochoa,Paola (2016)
ABSTRACT OBJECTIVE To analyze the relations between the meanings of working and the levels of doctors work well-being in the context of their working conditions. METHOD The research combined the qualitative methodology of textual analysis and the quantitative one of correspondence factor analysis. A convenience, intentional, and stratified sample composed of 305 Spanish and Latin American doctors completed an extensive questionnaire on the topics of the research. RESULTS The general meaning of working for the group located in the quartile of malaise included perceptions of discomfort, frustration, and exhaustion. However, those showing higher levels of well-being, located on the opposite quartile, associated their working experience with good conditions and the development of their professional and personal competences. CONCLUSIONS The study provides empirical evidence of the relationship between contextual factors and the meanings of working for participants with higher levels of malaise, and of the importance granted both to intrinsic and extrinsic factors by those who scored highest on well-being.